2021
DOI: 10.1128/aac.02476-20
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Fosmanogepix (APX001) for Intra-abdominal Candidiasis: from Lesion Penetration to Efficacy in a Mouse Model

Abstract: Intra-abdominal candidiasis (IAC) is one of the most common yet underappreciated form of invasive candidiasis. IAC is difficult to treat, and therapeutic failure and drug resistant breakthrough infections are common in some institutions despite the use of echinocandins as first line agents. Fosmanogepix (FMGX, formerly APX001) is a first-in-class antifungal prodrug that can be administered both intravenously and orally. FMGX is currently in Phase 2 clinical development for the treatment of life-threatening inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The mouse model of intra-abdominal candidiasis was performed as described previously (Lee et al, 2021). Briefly, 21 female CD1 mice (4-6 weeks old) were infected intraperitoneally with 100 μl cell suspension prepared in sterile stool matrix containing 2 Â 10 7 CFU of C. albicans on day 0.…”
Section: Antifungal Effects Of Holotoxin a 1 In The Mouse Model Of In...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse model of intra-abdominal candidiasis was performed as described previously (Lee et al, 2021). Briefly, 21 female CD1 mice (4-6 weeks old) were infected intraperitoneally with 100 μl cell suspension prepared in sterile stool matrix containing 2 Â 10 7 CFU of C. albicans on day 0.…”
Section: Antifungal Effects Of Holotoxin a 1 In The Mouse Model Of In...mentioning
confidence: 99%
“…The prevalence of intraabdominal candidiasis was about 4.7 per 1000 (Azim et al, 2017). The intra-abdominal candidiasis models are widely used to investigate the virulence mechanisms of C. albicans (Ashizawa et al, 2019) and to evaluate the therapeutic effects of antifungal agents for systematic fungal infection (Lee et al, 2020(Lee et al, , 2021. In this study, we found that holotoxin A 1 showed potent therapeutic effects in intra-abdominal candidiasis by decreasing the fungal burden in liver, spleen and kidney without signs of systemic toxicities, suggesting holotoxin A 1 as a promising candidate for the treatment of intra-abdominal candidiasis.…”
Section: Holotoxin a 1 Inhibited Intra-abdominal Candidiasis In Micementioning
confidence: 99%
“… 72 , 73 In a murine model of IAC, repeated doses of fosmanogepix could achieve good penetration in liver abscesses after 3 days and its efficacy in reducing liver fungal burden was superior to that of micafungin. 74 The penetration of fosmanogepix into the CNS was analyzed in one rabbit model of C. albicans IC and one murine model of C. auris IC. 73 , 75 In rabbits, the CNS tissue / plasma concentration ratio was 1 and fosmanogepix treatment achieved significant reduction in CNS fungal burden ( C. albicans ) for concentrations ranging from 25 to 100 mg/kg bid.…”
Section: Novel Antifungal Agents For Invasive Candidiasismentioning
confidence: 99%
“…This enzyme is responsible for adding an acyl group to the inositol unit of glucosaminyl phosphatidylinositol (GlcN-PI), a key step in the biosynthesis of GPI anchors . The active compound of fosmanogepix, manogepix, has broad spectrum activity, including antifungal effects against Candida spp., Cryptococcus spp., Aspergillus spp., Fusarium spp., Scedosporium spp., and L. prolificans . Fosmanogepix can reach the central nervous system, which places this drug as potential candidate to fight cryptococcal meningitis. ,,, A recent study in mice demonstrated that fosmanogepix is synergistic with amphotericin B against invasive pulmonary aspergillosis, invasive mucormycosis, and invasive fusariosis …”
Section: Antifungals Under Developmentmentioning
confidence: 99%